A study of water quality for Sungai Perlis during High Tide and Low Tide - Nur Shahidah Mohd Nasir (Penerbit Universiti Malaysia Perlis, 2010)
Sungai Perlis is the main river in Perlis with length is approximately 9.55 km from Kangar city to Kuala Perlis before discharged to the sea. The size of the Sungai Perlis basin is approximately 310 km2. The objectives of this study are to establish the pollutants profile along Sungai Perlis during high tide and low tide based on physical, chemical and biological parameter. The analysis involved in situ measurement for temperature, conductivity, salinity and pH.While laboratory analysis are COD, BOD, DO, SS, AN, Phosphate, Copper and E- Coli. During high tide, the high concentration of pollutant load for pH is 7.77, SS is 128 mg/l, DO is 8.2 mg/l, BOD is 4.5 mg/l, COD is 35.2 mg/l, AN is 1.28 mg/l, phosphate is 0.45 mg/l, Copper is 0.72 mg/l and E-Coli is 1011.2 MPN/100ml. During low tide the high concentration of pollutant load for pH is 6.96, SS is 228 mg/l, DO is 7.24 mg/l, BOD is 8.6 mg/l, COD is 56.5 mg/l, AN is 1.58 mg/l, phosphate is 0.88 mg/l, Copper is 0.44 mg/l and E-Coli is 1011.2 MPN/100ml. Along Sungai Perlis, there are residential area, agriculture areas, recreational park and a squatter located at Kuala Perlis, aquaculture ponds and Kangar wet market which are directly and indirectly affect the water quality of Sungai Perlis during high tide and low tide.